Oxygen vacancy promoted methane partial oxidation over iron oxide oxygen carriers in the chemical looping process. Issue 47 (21st November 2016) - Cheng, Zhuo; Qin, Lang; Guo, Mengqing; Xu, Mingyuan; Fan, Jonathan A.; Fan, Liang-Shih
Abstract : We found that oxygen vacancies can promote CH4 partial oxidation on iron oxide oxygen carriers during the chemical looping process. Abstract : We perform ab initio DFT+ U calculations and experimental studies of the partial oxidation of methane to syngas on iron oxide oxygen carriers to elucidate the role of oxygen vacancies in oxygen carrier reactivity. In particular, we explore the effect of oxygen vacancy concentration on sequential processes of methane dehydrogenation, and oxidation with lattice oxygen. We find that when CH4 adsorbs onto Fe atop sites without neighboring oxygen vacancies, it dehydrogenates with CH x radicals remaining on the same site and evolves into CO2 via the complete oxidation pathway. In the presence of oxygen vacancies, on the other hand, the formed methyl (CH3 ) prefers to migrate onto the vacancy site while the H from CH4 dehydrogenation remains on the original Fe atop site, and evolves into CO via the partial oxidation pathway. The oxygen vacancies created in the oxidation process can be healed by lattice oxygen diffusion from the subsurface to the surface vacancy sites, and it is found that the outward diffusion of lattice oxygen atoms is more favorable than the horizontal diffusion on the same layer. Based on the proposed mechanism and energy profile, we identify the rate-limiting steps of the partial oxidation and complete oxidation pathways. Also, we find that increasing the oxygen vacancy concentration not only lowers the barriers of CH4 dehydrogenation but also the cleavage energy of Fe–C bonds. However, the barrier of the rate-limiting step cannot further decrease when the oxygen vacancy concentration reaches 2.5%. The fundamental insight into the oxygen vacancy effect on CH4 oxidation with iron oxide oxygen carriers can help guide the design and development of more efficient oxygen carriers and CLPO processes.